Recommendations for the Implementation of Hospital Based HTA in Poland: Lessons Learned From International Experience - Gałązka-Sobotka, Małgorzata; Kowalska-Bobko, Iwona; Lach, Krzysztof; Mela, Aneta; Furman, Maciej; Lipska, Iga (Frontiers in Pharmacology, 2021)
Introduction: The main challenge of modern hospitals is purchasing medical technologies. Hospital-based health technology assessment is a conception used in healthcare facilities around the world to support management boards in providing relevant technologies for patients. Aim: The aim of this study was to update the existing body of knowledge on the characteristics of HB-HTA systems/models in the selected European countries. Insights gleaned from this study were used to inform an optimal approach while implementing HB-HTA in Poland. Material and methods: Firstly, we carried out a systematic review in Pubmed and Embase. secondly we searched for grey literature via the AdHopHTA online handbook and the design book of the AdHopHTA project, as well as literature describing healthcare systems provided by the WHO. Then, we conducted in-depth interviews with HB-HTA experts from four countries. Finally, we selected ten countries from Europe and prepared frameworks for data extraction and analysis. Results: The selected countries (Switzerland, Spain, France, Italy, Denmark, Finland, Sweden, the Netherlands and Austria) are examples of decentralised or deconcentrated healthcare systems. In terms of HB-HTA, they differ in terms of their respective organisational model (independent group, stand-alone, integrated-essential, integrated-specialized), type of financing (internally vs. externally), collaboration with an HTA National Agency and other stakeholders (e.g., Patients’ Associations). HB-HTA engages multi-skilled staff with various academic background and operates mainly as a voluntary structure. Conclusions: HB-HTA implementation in Poland should consider practices from experiences in different countries. Each country and each model of HB-HTA has its own strengths and weaknesses. Therefore, Poland’s HB-HTA model must be built responsibly, including different healthcare system stakeholders.